2003
DOI: 10.1038/sj.bjp.0705571
|View full text |Cite
|
Sign up to set email alerts
|

The Cl channel blocker niflumic acid releases Ca2+ from an intracellular store in rat pulmonary artery smooth muscle cells

Abstract: 1 The effect of the Cl À channel blockers niflumic acid (NFA), 5-nitro-2-(3-phenylpropylamino)-benzoic acid (NPPB), 4,4 0 -diisothiocyanatostilbene-2,2 0 -disulfonic acid (DIDS), and anthracene-9-carboxylic acid (A-9-C), on Ca 2 þ signalling in rat pulmonary artery smooth muscle cells was examined. Intracellular Ca 2 þ concentration ([Ca 2 þ ] i ) was monitored with either fura-2 or fluo-4, and caffeine was used to activate the ryanodine receptor, thereby releasing Ca 2 þ from the sarcoplasmic reticulum (SR). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 46 publications
1
28
2
Order By: Relevance
“…In rat pulmonary artery smooth muscle cells, niflumic acid has been noted to cause Ca 2+ release from intracellular stores (Cruickshank et al, 2003). However, the stimulatory effect seen here may not be due to such a mechanism since the concentration of niflumic acid utilized by these authors was of the order of 50 M, a much higher concentration than the one employed here.…”
Section: Role Of CL Channelscontrasting
confidence: 38%
“…In rat pulmonary artery smooth muscle cells, niflumic acid has been noted to cause Ca 2+ release from intracellular stores (Cruickshank et al, 2003). However, the stimulatory effect seen here may not be due to such a mechanism since the concentration of niflumic acid utilized by these authors was of the order of 50 M, a much higher concentration than the one employed here.…”
Section: Role Of CL Channelscontrasting
confidence: 38%
“…This diminished potency of NFA to inhibit I Cl(Ca) was also noticed by Piper et al (2002) in rabbit pulmonary myocytes dialyzed with elevated [Ca 2ϩ ] i (250 nM to 1 M). Whether the higher efficacy of NFA for blocking STICs relative to I Cl(Ca) elicited by a sustained elevated intracellular Ca 2ϩ level is caused by the much higher Ca 2ϩ concentrations (tens of micromolar) generated by Ca 2ϩ sparks (Jaggar et al, 2000) or the ability of NFA to interfere with Ca 2ϩ release from internal stores (Cruickshank et al, 2003) remains to be investigated. An alternative possibility is Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Flufenamic acid and tolfenamic acids relaxed guinea pig tracheal contractions through a direct inhibition of voltagegated Ca 2ϩ channels (Li et al, 1998). Niflumic acid stimulated Ca 2ϩ release from internal stores in rat pulmonary artery smooth muscle cells (Cruickshank et al, 2003) and was shown, along with 5-nitro-2-(3-phenylpropylamino)-benzoic acid and 4,4-diisothiocyanato-stilbene-2,2-disulfonic acid, to inhibit endothelin-1-induced contractions of rat pulmonary arterial myocytes by a mechanism independent of block of Cl Ca channels (Kato et al, 1999). Moreover, the IC 50 for NFA block of spontaneously occurring I Cl(Ca) is significantly lower than that required to block I Cl(Ca) evoked by caffeine or an agonist such as norepinephrine (Large and Wang, 1996).…”
mentioning
confidence: 99%
“…6). However, there have been reports of the related compound niflumic acid releasing Ca 2+ from ryanodine-sensitive stores that might act to reverse the affects on Ca 2+ -influx [17]. We also tested several di-and trivalent cations; neither Gd 3+ nor La 3+ at 300 μM blocked activation of CaMKII.…”
Section: Store-operated Ca 2+ -Permeable Channels Contribute To Camkimentioning
confidence: 99%